Digital Customer Experience of UNIPI Admission Website: A Technology Acceptance Model Analysis - Dikdik Firman Sidik; Muhammad Akil Hi Umar; Ihsan; Fadhil Qonia Zulfa; Agung Febriyadi Fazrin (JUSTINDO (Jurnal Sistem dan Teknologi Informasi Indonesia), 2026)
The digital transformation of academic services requires that university admission websites not only function informatively but also provide a positive digital experience. This study aims to analyze the influence of perceived usefulness and perceived ease of use on behavioral intention, mediated by Digital Customer Experience (DCX), within the Technology Acceptance Model (TAM) framework. An explanatory quantitative approach was employed through a survey of 200 prospective students using the admission website of Universitas Persatuan Islam. Data were analyzed using SEM-PLS with SmartPLS 4.0. The results indicate that perceived usefulness (β=0.452) and perceived ease of use (β=0.381) significantly affect DCX. DCX significantly influences behavioral intention (β=0.347) and partially mediates the effects of both exogenous variables. The model exhibits strong predictive power (R² DCX=0.648, R² BI=0.701). These findings offer an applicable DCX-TAM evaluation model to improve digital admission services in higher education.